Selection of dwarf cashew clones for the commercial plantation in the Ceará State, Brazil - Barros, Levi de Moura; Cavalcanti, José Jaime Vasconcelos; Paiva, João Rodrigues de; Crisóstomo, João Ribeiro; Corrêa, Maria Pinheiro Fernandes; Lima, Antônio Calixto (Pesquisa Agropecuaria Brasileira, 2000)
The main problem to Brazilian cashew growers is the orchard low productivity, presently below 220 kg ha-1 year-1 of nuts. For this reason, obtaining new selections is the main research goal. In this paper, the results of the evaluation of thirty rain-fed dwarf cashew clones (including four controls) carried out from April/1990 to February/1997 at the Estação Experimental, at Pacajus, CE, Brazil, are presented. The experimental design was in randomized blocks with four replications and four plants per plot, spaced 7 m x 7 m. The results revealed that the clones CAP 01, CAP 05 and CAP 12 with 70% average higher than the controls (2.4 m) have a medium canopy size between the common type and the dwarf type. The canopy diameter of the clones CAP 10, CAP 06 and CAP 26 was 63% higher than the controls (4.8 m) and the clones CAP 02, CAP 07, CAP 24 and CAP 25 showed the lowest values for this trait. Nut yield of the clones CAP 12, CAP 18 and CAP 26 was, respectively, 1,510; 1,281 and 1,262 kg ha-1 at the fifth year, that is, 175% higher than that of the best control, and the clones CAP 12 and CAP 18 were the most regular among all clones during the evaluation period. The kernel weight ranged from 1.9 to 3.2 g and 16 clones presented kernel weighting more than 2.5 g which are the most valuable in the international market. Four clones presented kernel percentage (29.4% to 30.6%) higher than the best control (28.1%) which means 38% over the industrial average (22%), and the clones CAP 11, CAP 06, and CAP 05 had less than 2% of broken kernel. The results pointed out the CAP 06 and CAP 26 clones as the most promising ones.